STUDI TENTANG PERILAKU NARSISME PADA PESERTA DIDIK KELAS VIII SMP NEGERI 1 NANGA MAHAP - Meldawati, Heni; Asrori, H.M.; Yuline, Yuline (Universitas Tanjungpura, 2023)
This study aims to analyze and describe the narcissistic behavior ofClass VIII students of SMP Negeri 1 Nanga Mahap in 2022. Theproblem of this research is: